Storytelling Through Paper Puppets to Enhance Early Childhood Language Development - Lilis Rahmawati; Dewi Zulfiana (Mentari : Journal of Islamic Primary School, 2025)
This study aims to describe the implementation of the storytelling method using paper puppets to improve the language skills of Group B children at RA An-Nuroh. The research employed a descriptive qualitative approach with 23 children aged 5–6 years as subjects in the 2024/2025 academic year. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that the use of paper puppet media was effective in enhancing children’s language skills, particularly in enriching vocabulary, constructing sentences, and building speaking confidence. The implementation of the storytelling method with paper puppets consisted of three stages: introduction, main activity, and closing. The main obstacle encountered was a noisy classroom environment. The solution applied was to create a more conducive classroom setting and include an ice-breaking activity before the lesson began. These findings indicate that paper puppets can serve as a creative and enjoyable alternative medium to support the language development of early childhood learners